Computational science and its applications -- ICCSA 2017 : 17th International Conference, Trieste, Italy, July 3-6, 2017, Proceedings.: 17th International Conference, Trieste, Italy, July 3-6, 2017, Proceedings. Part II (2017) - Unknown
No abstract available